The sexual politics of the head: the legal history of the veil - Nel, Philip (University of the Free State, 2002)
To trace the origins of legal provisions pertaining to the veiling of women, Mesopotamian legal documents of the early second and first millennia BCE are scrutinized in order to determine their first entries regarding the veil, the specific intentions of the legislator, and the cultural background of the legislation. Were the investigation to reveal only the material detail of the first legislation on veiling, the historical impact of patriarchy would remain obscure. Consequently the introduction of the veiling laws is evaluated against the background of a tradition of patriarchy which had a total disregard for the equality of women and reified their sexuality. The importance of this aspect lies in the fact that this inculcated degradation of women persists, even without the veil, in contemporaneous patriarchal societies. However, marked changes in the “sexual politics of the head” are currently discernible nationalist movements within Muslim countries and communities.

Met die oogmerk om die oorsprong en konteks van die regsvoorskrifte wat verband hou met die sluiering van vroue te bepaal, word die vroegste Mesopotamiese regsdokumente van die tweede en eerste millennia vC deurgewerk om die bedoeling en die kulturele konteks van die eerste regsinskrywings te bepaal. Indien die ondersoek sou stop by die behandeling van die materiële evidensie van die regsvoorskrifte ten opsigte van die sluier, sal die beslissende rol van patriargie nie duidelik blyk nie. Daarom word die wetgewing oor die sluier geëvalueer teen die agtergrond van ’n patriargale tradisie wat die gelyke regte van vroue verontagsaam en vroue en hul seksualiteit geobjektiveer het (reïfikasie). Dit word aangetoon dat die ingeburgerde tradisie van die onderwaardering van vroue verder strek as die sluier en steeds voortgesit word in huidige patriargale samelewings. Daar is egter tans besliste veranderings in die “seksuele politiek van die kop” binne nasionalitiese bewegings in Muslimlande en -gemeenskappe.
Keywords: Veiling of women; Veiling laws; Tradition of patriarchy; Equality of women